Green anti-ablation composite coating on surface of light alloy and preparation method of green anti-ablation composite coating

By forming a ceramic layer containing ZrO2-reinforced phase on the surface of the light alloy and combining it with the inorganic green coating, the problem of difficulty in taking into account the ablation resistance and green camouflageability of the light alloy surface is achieved, and the ablation resistance and green coating at high temperatures are achieved Camouflage effect, suitable for military vehicles and other fields.

CN119243288AInactive Publication Date: 2025-01-03XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411780853.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing light alloy surface anti-ablation coating is difficult to take into account both green camouflage and high-temperature anti-ablation properties. The microporous structure of the microarc oxide layer is prone to cracking at high temperatures. The existing green coating contains organic components that are not resistant to high temperatures.

Method used

The microarc oxidation method is used to form a ceramic layer containing ZrO2-reinforced phase on the surface of the light alloy, and the inorganic green coating is uniformly mixed on the surface of the ceramic layer to achieve mechanical interlock between the ceramic layer and the green coating, forming a dense inner layer and a porous outer layer. layer to enhance ablation resistance and green camouflage effect.

Benefits of technology

It realizes the ablation resistance and green camouflage function when the high-temperature flame airflow erosion on the surface of light alloy. The coating does not change color at high temperature and is environmentally friendly. It is suitable for light alloy surfaces such as magnesium, aluminum, and titanium. It has a simple process and is easy to produce industrially. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243288A_ABST
    Figure CN119243288A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metal material surface treatment, in particular to a light alloy surface green anti-ablation composite coating and a preparation method thereof. The preparation method of the composite coating comprises the following steps: preparing a micro-arc oxidation electrolyte, and preparing a ceramic layer containing a ZrO2 reinforced phase on the surface of a light alloy through a micro-arc oxidation method based on the electrolyte; wherein the electrolyte comprises sodium dihydrogen phosphate, potassium fluozirconate, zirconium sol and hydroxyethyl cellulose; preparing a film-forming agent and a filler of the green coating, uniformly mixing the film-forming agent and the filler, and coating the surface of the ceramic layer with the mixture to obtain a composite coating; wherein the composite coating is green. The composite coating provided by the invention can improve the ablation resistance of the light alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal material surface treatment, and in particular to a green anti-ablation composite coating on a light alloy surface and a preparation method thereof. Background Art

[0002] Light alloys such as aluminum, magnesium, and titanium have the advantages of low density, high specific strength, good shock absorption and casting performance. They are ideal lightweight materials and are widely used in military vehicle components such as weapons and armor, thereby significantly reducing the weight of the vehicle and improving mobility. However, weapons and armor of military vehicles will inevitably be subject to high-temperature ablation during service. Aluminum alloys and magnesium alloys have low melting points and poor high-temperature resistance. The oxide film formed by titanium alloys in high-temperature environments is loose, which seriously limits their application. On the other hand, the surfaces of weapons and armor of military vehicles also need to be green camouflaged to reduce the conspicuity of the target and improve its battlefield survivability. Therefore, it is necessary to prepare a green anti-ablation coating on the surface of light alloy weapons and armor.

[0003] The commonly used anti-ablation coating preparation technologies for light alloys mainly include supersonic flame spraying, plasma spraying, physical / chemical vapor deposition, anodizing, micro-arc oxidation and adhesive coating technology. The micro-arc oxidation process can form a high-melting point and high-temperature resistant ceramic layer in situ on the surface of the light alloy, and it also has a high membrane-base bonding force, which helps to improve the ablation resistance of the light alloy. However, there are a large number of microporous structural units in the micro-arc oxidation layer, which will crack under the action of thermal stress, and the ablation resistance of the film layer still has a lot of room for improvement. In addition, in order to achieve a green camouflage effect, a green camouflage layer needs to be coated on the surface. However, the existing green coating contains a large amount of organic components, and the coating is not resistant to high-temperature ablation. Therefore, it is difficult for existing coatings to achieve both green camouflage and ablation resistance on the surface of light alloys.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present disclosure is to provide a green anti-ablation composite coating on the surface of a light alloy and a preparation method thereof, aiming to solve the problem of low ablation resistance of the light alloy.

[0006] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.

[0007] According to one aspect of an embodiment of the present disclosure, a method for preparing a green anti-ablation composite coating on a light alloy surface is provided, comprising: A micro-arc oxidation electrolyte is prepared, and a ceramic layer containing a ZrO2 reinforcement phase is prepared on the surface of a light alloy by a micro-arc oxidation method based on the micro-arc oxidation electrolyte; wherein the micro-arc oxidation electrolyte comprises sodium dihydrogen phosphate, potassium fluorozirconate, zirconium sol, and hydroxyethyl cellulose; A film former and a filler for green coating are prepared, and the film former and the filler are uniformly mixed and then coated on the surface of the ceramic layer to obtain a composite coating; wherein the composite coating is green.

[0008] According to some embodiments of the present disclosure, based on the aforementioned scheme, the micro-arc oxidation electrolyte includes 5~20 g / L of sodium dihydrogen phosphate, 1~10 g / L of potassium fluorozirconate, 5~30 g / L of zirconium sol, and 0.5~5 g / L of hydroxyethyl cellulose.

[0009] According to some embodiments of the present disclosure, based on the aforementioned scheme, the process parameters of the micro-arc oxidation method are: the micro-arc oxidation voltage is 350 V ~ 550 V, the duty cycle is 10% ~ 50%, and the operating frequency is 100 Hz ~ 2000 Hz.

[0010] According to some embodiments of the present disclosure, based on the aforementioned scheme, the film-forming agent includes liquid potassium silicate, silica sol and condensed aluminum phosphate.

[0011] According to some embodiments of the present disclosure, based on the aforementioned scheme, the film-forming agent for preparing the green coating comprises: 45 to 90 parts of liquid potassium silicate, 5 to 45 parts of silica sol and 1 to 10 parts of condensed aluminum phosphate curing agent are mechanically stirred for a preset time to obtain the film-forming agent.

[0012] According to some embodiments of the present disclosure, based on the aforementioned scheme, the filler includes chromium oxide, red iron oxide, aluminum oxide, magnesium oxide and bentonite.

[0013] According to some embodiments of the present disclosure, based on the above scheme, the filler for preparing green coatings includes: 25 to 30 parts of chromium oxide, 55 to 60 parts of red iron oxide, 4 to 8 parts of aluminum oxide, 4 to 8 parts of magnesium oxide, and 2 to 4 parts of bentonite are ball-milled and mixed for a preset time; wherein the bentonite is selected from at least one of sodium-based bentonite and calcium-based bentonite.

[0014] According to some embodiments of the present disclosure, based on the above scheme, the film-forming agent and the filler are uniformly mixed and then applied to the surface of the ceramic layer to obtain a composite coating, including: The film-forming agent and the filler are mixed in a mass ratio of 1:1 to 5:1, and ultrasonic stirring is performed for a preset time to obtain a mixed solution; The mixed solution is sprayed or brushed onto the surface of the dried ceramic layer, and after a preset time at room temperature, it is cured at 120° C. for 2 h to obtain a composite coating.

[0015] According to some embodiments of the present disclosure, based on the aforementioned solution, the light alloy is a magnesium alloy, an aluminum alloy or a titanium alloy.

[0016] According to a second aspect of an embodiment of the present disclosure, a composite coating is provided. The composite coating is obtained by using a preparation method of the composite coating as described in any one of the above.

[0017] The exemplary embodiments of the present disclosure may have some or all of the following beneficial effects: In the technical solutions provided by some embodiments of the present disclosure, on the one hand, the ceramic layer containing ZrO2 reinforcement phase formed in situ by micro-arc oxidation has a dense inner layer structure, which can hinder the reaction of the metal matrix with external oxygen at high temperature. At the same time, the porous structure of the surface layer enables the green coating to realize a "infiltration / coating" combined mechanism, thereby realizing mechanical interlocking to enhance the bonding force between the green camouflage layer and the micro-arc oxidation layer, thereby improving its ablation resistance; on the other hand, the green coatings provided by the present disclosure are all inorganic components and have no pollution to the environment. The composite coating constructed together with the micro-arc oxidation layer can withstand multiple erosion and ablation by high-temperature flame airflow without changing color and still appearing green, thereby achieving both the anti-ablation and green camouflage functions of the coating; on the other hand, the preparation method of the present disclosure has a wide range of applications, and can be used to prepare green anti-ablation composite coatings on the surfaces of light alloys such as magnesium, aluminum, and titanium, and the preparation process is simple, easy to operate, green and environmentally friendly, and suitable for industrial production.

[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 The schematic diagram shows a process flow of a method for preparing a green anti-ablation composite coating on a light alloy surface in an exemplary embodiment of the present disclosure.

[0020] Figure 2 The ablation process diagram of an aluminum alloy green anti-ablation composite coating according to exemplary embodiment 1 of the present disclosure is schematically shown.

[0021] Figure 3The surface microscopic morphology of a green anti-ablation composite coating on an aluminum alloy obtained in exemplary embodiment 1 of the present disclosure is schematically shown.

[0022] Figure 4 The microscopic morphology of the surface of an aluminum alloy green anti-ablation composite coating after ablation according to exemplary embodiment 1 of the present disclosure is schematically shown.

[0023] Figure 5 The ablation process diagram of an aluminum alloy green anti-ablation composite coating of Comparative Example 1 is schematically shown.

[0024] Figure 6 The surface microscopic morphology of an aluminum alloy green anti-ablation composite coating of Comparative Example 1 is schematically shown. DETAILED DESCRIPTION

[0025] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more comprehensive and complete and will fully convey the concept of the example embodiments to those skilled in the art.

[0026] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced without one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known methods, devices, implementations or operations are not shown or described in detail to avoid blurring the various aspects of the present disclosure.

[0027] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or in one or more hardware modules or integrated circuits, or in different networks and / or processor devices and / or microcontroller devices.

[0028] The flowcharts shown in the accompanying drawings are only exemplary and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps can be decomposed, and some operations / steps can be combined or partially combined, so the actual execution order may change according to actual conditions.

[0029] Light alloys such as aluminum, magnesium, and titanium have the advantages of low density, high specific strength, good shock absorption and casting performance. They are ideal lightweight materials and are widely used in military vehicle components such as weapons and armor, thereby significantly reducing the weight of the vehicle and improving mobility. However, weapons and armor of military vehicles will inevitably be subject to high-temperature ablation during service. Aluminum alloys and magnesium alloys have low melting points and poor high-temperature resistance. The oxide film formed by titanium alloys in high-temperature environments is loose, which seriously limits their application. On the other hand, the surfaces of weapons and armor of military vehicles also need to be green camouflaged to reduce the conspicuity of the target and improve its battlefield survivability. Therefore, it is necessary to prepare a green anti-ablation coating on the surface of light alloy weapons and armor.

[0030] The commonly used anti-ablation coating preparation technologies for light alloys mainly include supersonic flame spraying, plasma spraying, physical / chemical vapor deposition, anodizing, micro-arc oxidation and adhesive coating technology. The micro-arc oxidation process can form a high-melting point and high-temperature resistant ceramic layer in situ on the surface of the light alloy, and it also has a high membrane-base bonding force, which helps to improve the ablation resistance of the light alloy. However, there are a large number of microporous structural units in the micro-arc oxidation layer, which will crack under the action of thermal stress, and the ablation resistance of the film layer still has a lot of room for improvement. In addition, in order to achieve a green camouflage effect, a green camouflage layer needs to be coated on the surface. However, the existing green coating contains a large amount of organic components, and the coating is not resistant to high-temperature ablation. Therefore, it is difficult for existing coatings to achieve both green camouflage and ablation resistance on the surface of light alloys.

[0031] In order to achieve both the anti-ablation and green camouflage requirements of the light alloy surface, the present disclosure provides a method for preparing a green anti-ablation composite coating on the light alloy surface. The method uses a micro-arc oxidation method to form an anti-ablation ceramic layer containing a ZrO2 reinforcement phase in situ on the light alloy surface, and then immerses the micro-arc oxidation sample into the formulated green coating to block the micropores of the ceramic layer to form a barrier layer. The multi-microporous characteristics of the micro-arc oxidation layer enable the green coating to achieve a "infiltration / coating" combined mechanism, thereby achieving mechanical interlocking to enhance the bonding force between the green camouflage layer and the micro-arc oxidation layer. The green camouflage layer can cooperate with the micro-arc oxidation layer to protect the substrate from erosion and ablation by high-temperature flame airflow. In addition, the reagents required for this process are non-toxic, green and environmentally friendly, and easy to construct, and can be widely used in thermal protection of structural parts in the fields of aerospace, automobiles, and electronic devices.

[0032] The implementation details of the technical solution of the embodiment of the present disclosure are elaborated in detail below.

[0033] Figure 1 The schematic diagram of the process of preparing the green anti-ablation composite coating on the surface of the light alloy in the exemplary embodiment of the present disclosure is shown schematically. Figure 1 As shown, the preparation method of the composite coating includes steps S101 to S102: Step S101, preparing a micro-arc oxidation electrolyte, and preparing a ceramic layer containing a ZrO2 reinforcement phase on the surface of a light alloy by a micro-arc oxidation method based on the micro-arc oxidation electrolyte; wherein the micro-arc oxidation electrolyte comprises sodium dihydrogen phosphate, potassium fluorozirconate, zirconium sol, and hydroxyethyl cellulose; Step S102, preparing a film-forming agent and a filler for a green coating, and uniformly mixing the film-forming agent and the filler and applying them on the surface of the ceramic layer to obtain a composite coating; wherein the composite coating is green.

[0034] In the technical solutions provided by some embodiments of the present disclosure, on the one hand, the ceramic layer containing ZrO2 reinforcement phase formed in situ by micro-arc oxidation has a dense inner layer structure, which can hinder the reaction of the metal matrix with external oxygen at high temperature. At the same time, the porous structure of the surface layer enables the green coating to realize a "infiltration / coating" combined mechanism, thereby realizing mechanical interlocking to enhance the bonding force between the green camouflage layer and the micro-arc oxidation layer, thereby improving its ablation resistance; on the other hand, the green coatings provided by the present disclosure are all inorganic components and have no pollution to the environment. The composite coating constructed together with the micro-arc oxidation layer can withstand multiple erosion and ablation by high-temperature flame airflow without changing color and still appearing green, thereby achieving both the anti-ablation and green camouflage functions of the coating; on the other hand, the preparation method of the present disclosure has a wide range of applications, and can be used to prepare green anti-ablation composite coatings on the surfaces of light alloys such as magnesium, aluminum, and titanium, and the preparation process is simple, easy to operate, green and environmentally friendly, and suitable for industrial production.

[0035] Hereinafter, each step of the method for preparing the composite coating in this exemplary embodiment will be described in more detail with reference to the accompanying drawings and examples.

[0036] In step S101, a micro-arc oxidation electrolyte is prepared, and a ceramic layer containing a ZrO2 reinforcement phase is prepared on the surface of a light alloy by a micro-arc oxidation method based on the micro-arc oxidation electrolyte; wherein the micro-arc oxidation electrolyte includes sodium dihydrogen phosphate, potassium fluorozirconate, zirconium sol, and hydroxyethyl cellulose.

[0037] Specifically, in one embodiment of the present disclosure, the micro-arc oxidation electrolyte includes 5-20 g / L of sodium dihydrogen phosphate, 1-10 g / L of potassium fluorozirconate, 5-30 g / L of zirconium sol, and 0.5-5 g / L of hydroxyethyl cellulose.

[0038] The process parameters of the micro-arc oxidation method are: the micro-arc oxidation voltage is 350 V to 550 V, the duty cycle is 10% to 50%, the operating frequency is 100 Hz to 2000 Hz, and the processing time of the micro-arc oxidation method is 10 min to 30 min.

[0039] In one embodiment of the present disclosure, the light alloy is a magnesium alloy, an aluminum alloy or a titanium alloy.

[0040] In step S102, a film former and a filler of a green coating are prepared, and the film former and the filler are uniformly mixed and then applied to the surface of the ceramic layer to obtain a composite coating; wherein the composite coating is green.

[0041] The film-forming agent includes liquid potassium silicate, silica sol and condensed aluminum phosphate. Specifically, the specific steps of preparing the film-forming agent for green coating include: mechanically stirring 45 to 90 parts of liquid potassium silicate, 5 to 45 parts of silica sol and 1 to 10 parts of condensed aluminum phosphate curing agent for a preset time to obtain the film-forming agent, wherein the modulus of the liquid potassium silicate is 3.3 and the stirring time is 1 to 2 hours.

[0042] The filler includes chromium oxide, red iron oxide, aluminum oxide, magnesium oxide and bentonite. Specifically, the specific steps of preparing the filler of the green coating include: mixing 25 to 30 parts of chromium oxide, 55 to 60 parts of red iron oxide, 4 to 8 parts of aluminum oxide, 4 to 8 parts of magnesium oxide, and 2 to 4 parts of bentonite by ball milling for a preset time, such as a mixing time of 1 to 2 hours; wherein the bentonite is selected from at least one of sodium-based bentonite and calcium-based bentonite.

[0043] In one embodiment of the present disclosure, the film-forming agent and the filler are uniformly mixed and then applied to the surface of the ceramic layer to obtain a composite coating, comprising: mixing the film-forming agent and the filler in a mass ratio of 1:1 to 5:1, and using ultrasonic stirring for a preset time to obtain a mixed liquid; spraying or brushing the mixed liquid onto the surface of the dried ceramic layer, drying at room temperature for a preset time, and then curing at a preset temperature for a preset time to obtain a composite coating.

[0044] Specifically, the stirring time may be 30 min; the surface of the ceramic layer is dried at room temperature for 2 h, and then cured at 120° C. for 2 h to obtain a composite coating.

[0045] The beneficial effects of the technical solution of the present disclosure are described in detail below through specific embodiments.

[0046] Example 1 Step 1: Prepare a ceramic layer containing a ZrO2 reinforcement phase on the surface of the aluminum alloy by micro-arc oxidation. The composition of the micro-arc oxidation electrolyte includes: 20 g / L sodium dihydrogen phosphate, 10 g / L potassium fluorozirconate, 15 g / L zirconium sol, 2 g / L hydroxyethyl cellulose, the micro-arc oxidation voltage is 400 V, the duty cycle is 30%, the operating frequency is 500 Hz, and the processing time is 30 min.

[0047] Step 2: prepare a green coating film-forming agent by mixing 90 g of liquid potassium silicate with a modulus of 3.3 with 5 g of silica sol and 5 g of condensed aluminum phosphate curing agent, and mechanically stirring for 2 h to obtain a film-forming agent.

[0048] Step 3: Mix the green paint filler: ball-mill 30 g of chromium oxide, 60 g of red iron oxide, 4 g of aluminum oxide, 4 g of magnesium oxide and 2 g of calcium-based bentonite for 2 h to obtain the filler.

[0049] Step 4: Prepare a green anti-ablation composite coating. Mix 100 g of the prepared film-forming agent and 100 g of filler. After ultrasonic stirring for 30 min, spray the mixed solution onto the surface of the ceramic layer dried in step 1. After drying at room temperature for 2 h, cure it at 120 °C for 2 h to obtain a green anti-ablation composite coating.

[0050] Figure 2 The process diagram of ablation of an aluminum alloy green anti-ablation composite coating according to the exemplary embodiment 1 of the present disclosure is schematically shown. Figure 2 As shown, it can be observed that the coating surface is still military green during the continuous ablation process of high-temperature flame, with no obvious ablation marks, and has good ablation resistance.

[0051] Figure 3 The surface microscopic morphology of a green anti-ablation composite coating of an aluminum alloy according to the exemplary embodiment 1 of the present disclosure is schematically shown. Figure 3 As shown, it can be observed that the holes on the surface of the aluminum alloy micro-arc oxidation layer have been completely covered by the sealing layer.

[0052] Figure 4 The microscopic morphology of the surface of an aluminum alloy green anti-ablation composite coating after ablation is schematically shown in Example 1 of the present disclosure. Figure 4 As shown, this is the surface microscopic morphology of the aluminum alloy green anti-ablation composite coating obtained in Example 1 after ablation for 20 minutes. It can be observed that there are no obvious defects on the surface, the coating is fully capable of withstanding the erosion of high-temperature flame airflow, and has good anti-ablation effect.

[0053] Example 2 Step 1: Prepare a ceramic layer containing a ZrO2 reinforcement phase on the surface of the aluminum alloy by micro-arc oxidation. The composition of the micro-arc oxidation electrolyte includes: 15 g / L sodium dihydrogen phosphate, 5 g / L potassium fluorozirconate, 5 g / L zirconium sol, 0.5 g / L hydroxyethyl cellulose, the micro-arc oxidation voltage is 450 V, the duty cycle is 10%, the operating frequency is 2000 Hz, and the processing time is 10 min.

[0054] Step 2: prepare a green coating film-forming agent. Mix 45 g of liquid potassium silicate with a modulus of 3.3 with 45 g of silica sol and 10 g of condensed aluminum phosphate curing agent, and mechanically stir for 1 h to obtain a film-forming agent.

[0055] Step 3: Mix the green paint filler: ball-mill 25 g of chromium oxide, 55 g of red iron oxide, 8 g of aluminum oxide, 8 g of magnesium oxide and 4 g of sodium bentonite for 1 h to obtain the filler.

[0056] Step 4: Prepare a green anti-ablation composite coating. Weigh 100 g of the prepared film-forming agent and mix it with 20 g of filler. After ultrasonic stirring for 30 minutes, brush the mixed solution onto the surface of the ceramic layer dried in step 1. After drying at room temperature for 2 hours, cure it at 120°C for 2 hours to obtain a green anti-ablation composite coating.

[0057] Example 3 Step 1: Prepare a ceramic layer containing a ZrO2 reinforcement phase on the surface of the magnesium alloy by micro-arc oxidation. The composition of the micro-arc oxidation electrolyte includes: 10 g / L sodium dihydrogen phosphate, 6 g / L potassium fluorozirconate, 30 g / L zirconium sol, 5 g / L hydroxyethyl cellulose, the micro-arc oxidation voltage is 350 V, the duty cycle is 30%, the operating frequency is 1000 Hz, and the processing time is 20 min.

[0058] Step 2: prepare a green coating film-forming agent by mixing 55 g of liquid potassium silicate with a modulus of 3.3 with 44 g of silica sol and 1 g of condensed aluminum phosphate curing agent, and mechanically stirring for 2 h to obtain a film-forming agent.

[0059] Step 3: Mix the green paint filler: ball-mill 27 g of chromium oxide, 58 g of red iron oxide, 6 g of aluminum oxide, 6 g of magnesium oxide and 3 g of sodium bentonite for 2 h to obtain the filler.

[0060] Step 4: Prepare a green anti-ablation composite coating. Weigh 100 g of the prepared film-forming agent and mix it with 50 g of filler. After ultrasonic stirring for 30 min, brush the mixed solution onto the surface of the ceramic layer dried in step 1. After drying at room temperature for 2 h, cure it at 120 °C for 2 h to obtain a green anti-ablation composite coating.

[0061] Example 4 Step 1: Prepare a ceramic layer containing a ZrO2 reinforcement phase on the surface of the magnesium alloy by micro-arc oxidation. The composition of the micro-arc oxidation electrolyte includes: 5 g / L sodium dihydrogen phosphate, 10 g / L potassium fluorozirconate, 20 g / L zirconium sol, 3 g / L hydroxyethyl cellulose, the micro-arc oxidation voltage is 400 V, the duty cycle is 20%, the operating frequency is 100 Hz, and the processing time is 20 min.

[0062] Step 2: prepare a green coating film-forming agent by mixing 80 g of liquid potassium silicate with a modulus of 3.3 with 10 g of silica sol and 10 g of condensed aluminum phosphate curing agent, and mechanically stirring for 1 h to obtain a film-forming agent.

[0063] Step 3: Mix the green paint filler: ball-mill 25 g of chromium oxide, 60 g of red iron oxide, 6 g of aluminum oxide, 6 g of magnesium oxide and 3 g of sodium bentonite for 1 h to obtain the filler.

[0064] Step 4: Prepare a green anti-ablation composite coating. Weigh 100 g of the prepared film-forming agent and mix it with 25 g of filler. After ultrasonic stirring for 30 minutes, brush the mixed solution onto the surface of the ceramic layer dried in step 1. After drying at room temperature for 2 hours, cure it at 120 °C for 2 hours to obtain a green anti-ablation composite coating.

[0065] Example 5 Step 1: Prepare a ceramic layer containing a ZrO2 reinforcement phase on the surface of the titanium alloy by micro-arc oxidation. The composition of the micro-arc oxidation electrolyte includes: 5 g / L sodium dihydrogen phosphate, 20 g / L potassium fluorozirconate, 10 g / L zirconium sol, 1 g / L hydroxyethyl cellulose, the micro-arc oxidation voltage is 550V, the duty cycle is 50%, the operating frequency is 2000 Hz, and the processing time is 20 min.

[0066] Step 2: prepare a green coating film-forming agent by mixing 75 g of liquid potassium silicate with a modulus of 3.3 with 20 g of silica sol and 5 g of condensed aluminum phosphate curing agent, and mechanically stirring for 1 h to obtain a film-forming agent.

[0067] Step 3: Mix the green paint filler: ball-mill 28 g of chromium oxide, 57 g of red iron oxide, 7 g of aluminum oxide, 6 g of magnesium oxide and 2 g of sodium bentonite for 1 h to obtain the filler.

[0068] Step 4: Prepare a green anti-ablation composite coating. Weigh 100 g of the prepared film-forming agent and mix it with 30 g of filler. After ultrasonic stirring for 30 minutes, brush the mixed solution onto the surface of the ceramic layer dried in step 1. After drying at room temperature for 2 hours, cure it at 120 °C for 2 hours to obtain a green anti-ablation composite coating.

[0069] Example 6 Step 1: Prepare a ceramic layer containing a ZrO2 reinforcement phase on the surface of the titanium alloy by micro-arc oxidation. The composition of the micro-arc oxidation electrolyte includes: 20 g / L sodium dihydrogen phosphate, 5 g / L potassium fluorozirconate, 25 g / L zirconium sol, 4 g / L hydroxyethyl cellulose, the micro-arc oxidation voltage is 500V, the duty cycle is 40%, the operating frequency is 300 Hz, and the processing time is 30 min.

[0070] Step 2: prepare a green coating film-forming agent by mixing 60 g of liquid potassium silicate with a modulus of 3.3 with 30 g of silica sol and 10 g of condensed aluminum phosphate curing agent, and mechanically stirring for 2 h to obtain a film-forming agent.

[0071] Step 3: Mix the green paint filler: ball-mill 26 g of chromium oxide, 59 g of red iron oxide, 8 g of aluminum oxide, 4 g of magnesium oxide and 3 g of sodium bentonite for 2 h to obtain the filler.

[0072] Step 4: Prepare a green anti-ablation composite coating. Weigh 100 g of the prepared film-forming agent and mix it with 60 g of filler. After ultrasonic stirring for 30 min, brush the mixed solution onto the surface of the ceramic layer dried in step 1. After drying at room temperature for 2 h, cure it at 120 °C for 2 h to obtain a green anti-ablation composite coating.

[0073] Comparative Example 1 The difference between this comparative example and Example 1 is that in step one, a ceramic layer without a ZrO2 reinforcing phase is prepared on the surface of the aluminum alloy by a micro-arc oxidation method, the micro-arc oxidation electrolyte is 20 g / L sodium dihydrogen phosphate, the micro-arc oxidation voltage is 400 V, the duty cycle is 30%, the operating frequency is 500 Hz, and the processing time is 30 min.

[0074] Figure 5 The ablation process diagram of a green anti-ablation composite coating of aluminum alloy in comparative example 1 is schematically shown. It can be observed that ablation spots appear on the surface of the coating after continuous ablation by high-temperature flame for 4 minutes, and the ablated area appears grayish white.

[0075] Figure 6 The schematic diagram shows the surface microscopic morphology of an aluminum alloy green anti-ablation composite coating of Comparative Example 1, i.e., the surface microscopic morphology of the aluminum alloy green anti-ablation composite coating of Comparative Example 1 after ablation for 4 minutes. It can be observed that a large number of cracks appear on the surface, the coating cannot continuously withstand the erosion of the high-temperature flame airflow, and the anti-ablation performance is poor.

[0076] Aluminum alloy, magnesium alloy and titanium alloy substrates are used as comparative examples for comparison with the embodiments.

[0077] The green anti-ablation composite coatings provided in the above-mentioned Examples 1 to 6 and Comparative Example 1 were subjected to flame ablation tests, and the test results are shown in Table 1.

[0078] Table 1

[0079] As shown in Table 1, the ablation resistance time of the green anti-ablation composite coatings provided in Examples 1 to 6 is significantly improved compared with that of the alloy substrate. The ablation resistance time of the aluminum alloy substrate without the coating is 2 minutes, while the ablation resistance time of the aluminum alloy can be increased to 25 minutes after the coating is applied. For the magnesium alloy and titanium alloy substrates, the ablation resistance time after the coating is applied is also increased from 1 minute and 5 minutes to 15 minutes and 40 minutes, respectively. Figure 4 and Figure 6From the surface microscopic morphology of the green anti-ablation composite coating of the aluminum alloy described in Example 1 and Comparative Example 1 after ablation, it can be seen that the surface of the film layer described in Example 1 is still intact and defect-free after being ablated by the flame for a longer time, and the micro-arc oxidation coating containing the ZrO2 reinforcement phase can block the external oxygen from reacting with the substrate, thereby giving the composite coating a longer-lasting ablation resistance.

[0080] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.

[0081] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing a green anti-ablation composite coating on a light alloy surface, characterized in that: include: A micro-arc oxidation electrolyte is prepared, and a ceramic layer containing a ZrO2 reinforcement phase is prepared on the surface of a light alloy by a micro-arc oxidation method based on the micro-arc oxidation electrolyte; wherein the micro-arc oxidation electrolyte comprises sodium dihydrogen phosphate, potassium fluorozirconate, zirconium sol, and hydroxyethyl cellulose; A film former and a filler for green coating are prepared, and the film former and the filler are evenly mixed and then coated on the surface of the ceramic layer to obtain a composite coating; wherein the composite coating is green.

2. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 1, characterized in that: The micro-arc oxidation electrolyte comprises 5-20 g / L of sodium dihydrogen phosphate, 1-10 g / L of potassium fluorozirconate, 5-30 g / L of zirconium sol, and 0.5-5 g / L of hydroxyethyl cellulose.

3. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 1, characterized in that: The process parameters of the micro-arc oxidation method are: micro-arc oxidation voltage is 350 V ~ 550 V, duty cycle is 10% ~ 50%, and operating frequency is 100 Hz ~ 2000 Hz.

4. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 1, characterized in that: The film-forming agent comprises liquid potassium silicate, silica sol and condensed aluminum phosphate.

5. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 4, characterized in that: The film-forming agent for preparing green coating comprises: 45 to 90 parts of liquid potassium silicate, 5 to 45 parts of silica sol and 1 to 10 parts of condensed aluminum phosphate curing agent are mechanically stirred for a preset time to obtain the film-forming agent.

6. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 1, characterized in that: The fillers include chromium oxide, red iron oxide, aluminum oxide, magnesium oxide and bentonite.

7. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 6, characterized in that: The filler for preparing green coating comprises: 25 to 30 parts of chromium oxide, 55 to 60 parts of red iron oxide, 4 to 8 parts of aluminum oxide, 4 to 8 parts of magnesium oxide, and 2 to 4 parts of bentonite are ball-milled and mixed for a preset time; wherein the bentonite is selected from at least one of sodium-based bentonite and calcium-based bentonite.

8. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 1, characterized in that: The step of uniformly mixing the film-forming agent and the filler and coating the mixture on the surface of the ceramic layer to obtain a composite coating comprises: The film-forming agent and the filler are mixed in a mass ratio of 1:1 to 5:1, and ultrasonic stirring is performed for a preset time to obtain a mixed solution; The mixed liquid is sprayed or brushed onto the surface of the dried ceramic layer, dried at room temperature for a preset time, and then cured at a preset temperature for a preset time to obtain a composite coating.

9. The method for preparing a green anti-ablation composite coating on a light alloy surface according to claim 1, characterized in that: The light alloy is a magnesium alloy, an aluminum alloy or a titanium alloy.

10. A green anti-ablation composite coating on the surface of a light alloy, characterized in that: The composite coating is obtained by using the preparation method of the composite coating according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ceramic coating material with characteristics of high-temperature resistance, high blackness, coking resistance and corrosion resistance

    CN108299870A

  • Metal surface heat protecting coating structure and preparation method and composite material thereof

    CN111593348A

  • Chopped carbon fiber reinforced aluminum silicate ceramic-based composite material and preparation method thereof

    CN111718180A

  • Method for preparing red and green coatings on surface of titanium alloy

    CN113089050A

  • ZrO2 / MgO wear-resistant film layer on magnesium alloy and preparation method thereof

    CN113089053A